Empowering Women : The Effect of Women’s Decision-Making Power on Reproductive Health Services Uptake - Evidence from Pakistan - Hou, Xiaohui; Ma, Ning (2012)
A large body of research has attempted to explore the links between women's autonomy and their uptake of reproductive health services in the South Asia region, but the evidence so far is inconclusive. This study uses the Pakistan Social and Living Standards Measurement Survey to examine the influence of household decision making on women's uptake of reproductive health services. The analysis finds that women's decision-making power has a significant positive correlation with reproductive health services uptake and that influential males' decision-making power has the opposite effect, after controlling for socio-economic indicators and supply-side conditions. The findings suggest that empowering women and increasing their ability to make decisions may increase their uptake of reproductive health services. They also suggest that policies directed toward improving women's utilization of maternity services must target men as well as women in Pakistan.